Administrasi Pendidikan dalam Perspektif Pendidikan Agama Islam: Konsep, Prinsip, dan Tantangan Kontemporer - Fatimah, Meti; Widyaningsih, Erna (TSAQOFAH, 2026)
Educational administration is a comprehensive process that ensures the achievement of educational objectives effectively and efficiently through the planning, organizing, directing, supervising, and evaluating of all educational activities. This article aims to examine the concept of educational administration, including its aims, functions, principles, and scope, with a particular focus on the context of Pendidikan Agama Islam (PAI). A qualitative library study method was employed by analyzing theories and expert perspectives to understand the role of administration in realizing quality education. The findings indicate that educational administration does not only concentrate on technical managerial aspects, but is also grounded in philosophical, sociological, and spiritual dimensions, especially in Islamic education, which emphasizes moral values, discipline, and spirituality. The article concludes that robust educational administration is crucial for enhancing the effectiveness of learning, strengthening character formation, and preparing students to face global challenges while remaining firmly rooted in Islamic values.